The Effect Of The Traditional Fort Game On Improving The Physical Fitness Of Students At Sie State Elementary School - miskan, miskan; Samsudin, Samsudin; Salahudin, Salahudin; Nasrulah, Nasrulah; Furkan, Furkan; Yanti, Sri (Jurnal Ilmiah Mandala Education (JIME), 2025)
In today's digital era, it's clear that children prefer playing with gadgets to exercising or doing physical activities. This can interfere with students' physical fitness, so it's no wonder that many children today are less energetic, easily tired, and less mobile. This study aimed to determine the effect of traditional Bentenng games on increasing the physical fitness of SDN Sie students. This quantitative study used the pre-experiment method with 12 students as subjects. The sampling technique used was saturation sampling. Data were collected using the TKJI test instrument, which included the 40-meter run, elbow hanging (pull-up), 30-second sit-up, and upright jump tests. The students were then given treatment before and after the traditional fort game. Results of the homogeneity analysis showed a significance value of 0.516, which is greater than 0.05; therefore, the results (pre and post) are homogeneous. The normality test, using the Shapiro-Wilk test, showed significance values of 0.301 and 0.692 for the pre- and post-test data, respectively, indicating that the data were normally distributed at both measurement stages. The results of the two-sided paired sample t-test showed a significance value of 0.020, indicating a significant difference in the TKJI test results before and after the traditional fort game